The eco-innovation impact on economic and environmental performance of EU Member States - Mačiulytė-Šniukienė, Alma; Sekhniashvili, Dali (Business, Management and Economics Engineering, 2021)
Development of innovation is recognised as a most powerful tool for the economic growth of countries. However, their effects on the quality of the environment are still being debated. To achieve sustainable development, eco-innovation becomes significant. EU countries expand eco-innovation activities, but it is not clear whether its development achieves the goal of economic growth and improves the quality of the environment.Purpose – to present how EU Member States perform in economic growth, environment and eco-innovation development and to evaluate eco-innovations impact on economic and environmental performance.Research methodology – the random effect regression was used for investigation relationship between eco-innovation, economic growth and environmental performance.Findings – eco-innovation development influences not only EU MS economic growth but also has a positive effect on environmental performance.Research limitations – eco-innovations development and economic growth can be interdepended, but this research investigates just one-way dependence. Granger causality test can be used for relationship assessment in the future.Practical implications – the research results can be used for both the development of environmental policy and the policy of business support for eco-innovation implementation.Originality/Value – study results confirmed previous assessment results on eco-innovation and economic growth and provided new knowledge of their effect on environmental performance.